2019
DOI: 10.3389/fnins.2019.00354
|View full text |Cite
|
Sign up to set email alerts
|

One-Step, Three-Factor Passthought Authentication With Custom-Fit, In-Ear EEG

Abstract: In-ear EEG offers a promising path toward usable, discreet brain-computer interfaces (BCIs) for both healthy individuals and persons with disabilities. To test the promise of this modality, we produced a brain-based authentication system using custom-fit EEG earpieces. In a sample of N = 7 participants, we demonstrated that our system has high accuracy, higher than prior work using non-custom earpieces. We demonstrated that both inherence and knowledge factors contribute to authenticatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…2B shows the interindividual correlations (µ=0.45, σ=0.10) to be significantly below the intra-individual ones throughout the year. This gap is consistent with the within-subjects and betweensubjects similarity scores in [16], and is the basis underlying many brainwave-based authentication systems [21], [22], [23], [24], [25], [26], [27].…”
Section: A Long-term Stabilitysupporting
confidence: 78%
“…2B shows the interindividual correlations (µ=0.45, σ=0.10) to be significantly below the intra-individual ones throughout the year. This gap is consistent with the within-subjects and betweensubjects similarity scores in [16], and is the basis underlying many brainwave-based authentication systems [21], [22], [23], [24], [25], [26], [27].…”
Section: A Long-term Stabilitysupporting
confidence: 78%
“…Such research has for example found the suitability of ear-EEG for continuous daily observation [22], the observation of auditory attention processes [29,35,38,53,59], visual stimulation intensities [22,60], or sleep stage classification [51,56,66]. Due to the advanced understandings, recent work has also started to explore more HCI-related application scenarios like the monitoring of affect [4] and stress [45], biosignal based user authentication [48], and the recognition of mental gestures as user input information for active BCIs [49]. While this research represents a fascinating and growing development in the HCI domain, its progress is greatly impeded by a low degree of accessibility to the required components: (1) cost-effective amplifiers with open data access and (2) ready-to-use ear-EEG electrodes, and (3) the integration of both parts into wearable units that can be used in realistic HCI scenarios.…”
Section: Ear-based Sensing Researchmentioning
confidence: 99%
“…In recent years this paradigm has been extended to include three authentication factors by treating the BCI device itself as a physical authentication token. 15 In addition to the potential for single-step MFA, passthoughts provide several other benefits: 14 unlike other biometrics, they are cancelable or changeable, meaning that they can be revoked or changed in the event of a data breach; depending on the implementation, passthoughts can be immune to observation or shoulder-surfing attacks that are problematic for text passwords and many other Despite these factors, there remain unanswered questions regarding the public acceptance and adoption of passthoughts. It is generally understood that usability is a critical component of security systems, and that poor usability is itself a security vulnerability.…”
Section: Passthoughts: Brain-based Authenticationmentioning
confidence: 99%
“…Poulos, Rangoussi, and Alexandris 103 and Paranjape et al 104 published studies in 1999 and 2001 respectively demonstrating classification systems which could identify individuals from a small sample based on features of their EEG with accuracies between 80 and 100%. Since then a number of studies 15,[105][106][107][108][109] have implemented biometric authentication systems based on resting-state EEG with reasonable success, demonstrating that the uniqueness of individual users' EEGs is sufficient for biometric authentication, at least within a restricted population.…”
Section: Bcis For Authenticationmentioning
confidence: 99%
See 1 more Smart Citation